Comparison of marginal bone loss in SLA and RBM implants: A prospective cohort study - Nemati, Majid; Dadkhah, Bahar; Tabrizi, Reza; Shafiei, Shervin; Moslemi, Hamidreza (National journal of maxillofacial surgery, 2023)
Context: The study aims to answer the following question: Among the patients who received a dental implant, is there any difference in marginal bone loss (MBL) between sandblasted and acid-etched (SLA) and resorbable blast media (RBM) implants? Aims: The study aimed to evaluate marginal bone loss in SLA and RBM implants one year after loading. Settings and Design: A Prospective Cohort Study. Methods and Material: In this prospective cohort study with a pre-protocol population, subjects were assigned into two groups: Subjects received SLA implants in group 1 and RBM in group 2. MBL was assessed 12 months after loadings through digital parallel radiographs. Statistical Analysis Used: An Independent t-test was used to compare MBL between the two groups. Results: Sixty-six implants were studied (each group 33 implants). The mean of MBL in the RBM group was significantly higher than the SLA group (1.39 ± 0.31 mm, 0.89 ± 0.26 mm, respectively, P < 0.001). MBL in the mesial sides of implants in the RBM group was significantly higher than the SLA group (1.28 ± 0.29 mm, 0.8 ± 0.29 mm, respectively, P < 0.001). Analysis of the data demonstrated a significantly higher mean of MBL in the distal sides of implants in the RBM group than in the SLA group (1.51 ± 0.35 mm, 0.97 ± 0.27 mm, respectively, P < 0.001). In both groups, the mean of MBL on the distal side was significantly higher than on the mesial side (P < 0.05). Conclusions: Within this study's limitation, RBM implants showed significantly more MBL than SLA implants.